KNOWLEDGE, PRACTICE ON PREVENTION OF REPRODUCTIVE UTILITATIONS IN WOMEN 18-49 YEARS ACCEPTED AT DONG THAP PROVINECIAL CENTER FOR DISEASE CONTROL, IN 2021 (Vietnam Journal of Community Medicine, 2021)
Objective: To determine the rate of knowledge and correct practice on prevention of reproductive tract infections among women aged 18-49 years who visit a general clinic, Center for Disease Control of Dong Thap province.Methods: Cross-sectional study, with 421 study participants who were women 18-49 years old who visited the general clinic, Center for Disease Control of Dong Thap province. The study period was from August 2020 to June 2021. Research results: A total of 421 subjects participated in the study, the results of the general information characteristics showed that the majority of study subjects had the highest high school education with 48.7%, in terms of marriage, the majority of women are living with their husbands, accounting for 98.5%. In terms of occupation, housewives account for 45.4%, employees and civil servants account for 16.2%, families with an average living standard or higher account for 92.8%. The rate of knowledge achieved accounted for 46.1%, good practice accounted for 70.1%. The rate of reproductive tract infections accounted for 49.4%. The study showed that the relationship between knowledge and practice was statistically significant with p < 0.05. The relationship between knowledge and practice with the incidence of reproductive tract infections in women was not statistically significant (p>0.05).Conclusion: The rate of reproductive tract infections accounted for 49.4%, knowledge reached 46.1%, good practice accounted for 70.1%. There is a relationship between knowledge and practice.
Keywords: KAP on reproductive tract infections, Prevention of reproductive tract infections, Vaginitis in women 18-49 years old.